PENGARUH TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA DESA TERHADAP KINERJA PEMERINTAH DESA UTEUN GEULINGGANG,KRUENG GEUKUEH, ACEH UTARA - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
This study aims to examine the Influence of Transparency and Accountability of Village Fund Management To The Performance of Uteun Geulinggang Village Government, Krueng Geukueh, North Aceh. Data used in this research is primarydata as many as 38 sample with purposive sampling technique. The method used toanalyze between independent variables with dependent variable is multiple linearregression method and test of classical assumption. The simultaneous research results of transparency and accountability of village fund management have an effecton the performance of Village Government. While the results of partial researchvariables of transparency of village fund management have a significant effect on theperformance of Village Government, accountability variable of village fund management also have a significant effect to the performance of Uteun Geulinggang Village Government, Krueng Geukuh Aceh Utara.